Are self-employed really happier than employees? An approach modelling adaptation and anticipation effects to self-employment and general job changes - Dominik Hanglberger; Joachim Merz (Leuphana Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2011)
Empirical analyses using cross-sectional and panel data found significantly higher levels of job satisfaction for self-employed than for employees. We argue that those estimates in previous studies might be biased by neglecting anticipation and adaptation effects. For testing we specify several models accounting for anticipation and adaptation to self-employment and job changes. Based on data from the German Socio-Economic Panel Survey (SOEP) we find that becoming self-employed is associated with large negative anticipation effects. In contrast to recent literature we find no specific long term effect of self-employment on job satisfaction. Accounting for anticipation and adaptation to job changes in general, which includes changes between employee jobs, reduces the effect of self-employment on job satisfaction by 70%. When controlling for anticipation and adaptation to job changes, we find no further anticipation effect of self-employment and a weak positive but not significant effect of self-employment on job satisfaction for three years. Thus adaptation wipes out higher satisfaction within the first three years being self-employed. According to our results previous studies at least overestimated possible positive effects of self-employment on job satisfaction. – – Zahlreiche empirische Analysen kamen zu dem Ergebnis, dass Selbständige ein höheres Niveau an Arbeitszufriedenheit erreichen als abhängig Beschäftigte. Dieses Ergebnis wurde sowohl durch Querschnittsanalysen bestätigt, als auch durch Studien, die auf Paneldaten basieren. In unserem Beitrag diskutieren wir, ob dieses empirische Ergebnis möglicherweise auf die Vernachlässigung von Antizipations- und Adaptionseffekten zurückgeführt werden kann. Um den Sachverhalt empirisch zu überprüfen, spezifizieren wir fixed-effects Regressionsmodelle, die auch Antizipation und Adaption der Arbeitszufriedenheit an Selbständigkeit und Arbeitsplatzwechsel berücksichtigt. Grundlage für unsere Analyse ist das Soziooekonomische Panel (SOEP) der Jahre 1984-2009. Im Gegensatz zur existierenden Literatur findet sich keine positive Langzeitwirkung der Selbständigkeit, wenn Antizipation und Adaption berücksichtigt werden. Werden auch Antizipation und Adaption an Arbeitsplatzwechsel im Allgemeinen berücksichtigt, so reduziert sich der Effekt der Selbständigkeit auf die Arbeitszufriedenheit um 70%. In Modellen, die Antizipation und Adaption an Selbständigkeit und Arbeitsplatzwechsel berücksichtigen, finden sich keine separaten Antizipationseffekte der Selbständigkeit mehr. Lediglich für die ersten drei Jahre der Selbständigkeit findet sich noch ein im Durchschnitt positiver Effekt der Selbständigkeit, der allerdings nicht signifikant ist. Unsere Ergebnisse legen daher nahe, dass bisherige Studien die positive Wirkung der Selbständigkeit auf die Arbeitszufriedenheit zumindest deutlich überschätzen.
Keywords: J23; J28; J81; 330; job satisfaction; self-employment; hedonic treadmill model; adaptation; anticipation; fixed-effects panel estimations; German Socio-Economic Panel (SOEP); Arbeitszufriedenheit; Selbständige; hedonic treadmill; Adaption; Antizipation; fixed-effects Panelschätzungen; Sozio-oekonomisches Panel (SOEP); Selbstständige; Arbeitszufriedenheit; Erwerbsverlauf; Schätzung; Deutschland